Meta-analysis of efficacy and safety of bevacizumab in the treatment of hereditary hemorrhagic telangiectasia epistaxis - Chen, Huimin; Zhang, Zhiping; Chen, Xiaojuan; Wang, Chaoyu; Chen, Mingdi; Liao, Huizhao; Zhu, Jinru; Zheng, Zhenzhen; Chen, Riken (Frontiers in Pharmacology, 2023)
Objective: A meta-analysis is conducted to evaluate the effectiveness and safety of bevacizumab in hereditary hemorrhagic telangiectasia (HHT) epistaxis.: Two researchers search PubMed, EMBASE and Web of Science databases from their inception until September 3th, 2023. The literature is read and screened, and valid data extracted, collated and analyzed. Its quality is then assessed using the Cochrane risk assessment scale. This study uses Endnote 9.3 software for literature management and RevMan 5.3.1 software for evaluation. Results: A total of 7 documents met the requirements, including a total of 359 patients, and the literature quality evaluation was grade B. The Meta-analysis results showed that:Bevacizumab reduces the Epistaxis Severity Score (ESS) in patients with HHT epistaxis compared with the control [WMD = -0.22，95%CI (-0.38，-0.05)，P=0.01]. However, there is no significant effect on duration of epistaxis [WMD = -15.59，95%CI (-70.41，39.23),P=0.58] and number of epistaxes [WMD = -1.27,95%CI(-10.23,7.70),P=0.78] in patients with HHT epistaxis. In terms of adverse effects, there is no significant difference between the bevacizumab group and control group [OR = 1.36, 95% CI (0.54,3.44), P = 0.52].Bevacizumab is superior to the control group in the treatment of HHT epistaxis, and adverse reactions are not further increased in the bevacizumab group than in the control group, suggesting that bevacizumab has clinical value in the treatment of HHT epistaxis.